2022
DOI: 10.3389/fonc.2022.911397
|View full text |Cite
|
Sign up to set email alerts
|

Preferred place of death and end-of-life care for adult cancer patients in Iran: A cross-sectional study

Abstract: BackgroundMore than 50,000 deaths in terms of cancer occur annually in Iranian hospitals. Determining the preferred place of end-of-life care and death for cancer patients in Iran is a quality marker for good end-of-life care and good death. The purpose of this study was to determine the preferred place of end-of-life care and death in cancer patients.MethodIn 2021, the current descriptive cross-sectional investigation was carried out. Using the convenience sample approach, patients were chosen from three Tehr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…A recent study by Fereidouni et al reported that over 75% of a group of Iranian advanced cancer patients preferred to die at home [25]. The concordance between the patient's preferred PoD and the actual PoD is an important indicator of the effectiveness of palliative care services [41], though, we did not include patients' preferences in our study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A recent study by Fereidouni et al reported that over 75% of a group of Iranian advanced cancer patients preferred to die at home [25]. The concordance between the patient's preferred PoD and the actual PoD is an important indicator of the effectiveness of palliative care services [41], though, we did not include patients' preferences in our study.…”
Section: Discussionmentioning
confidence: 94%
“…Access to palliative care in Iran is limited to the services provided by the "Iranian Cancer Control Center" (aka MACSA, formerly "Ala Cancer Control Center"), the largest provider of palliative care services in Iran, and a few hospital-based palliative care programs [24]. However, a study performed in 2022 in Iran indicated that 75% of patients with advanced cancer preferred to stay at home at the end of their lives [25]. Iranian caregivers and nurses also agree that patients' death at home is preferred over other places [26].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, certain patients in the intervention group declined to express their thoughts and preferences regarding death and decision-making. This reluctance may be attributed to cultural factors, as there is a prevailing belief in Iranian culture that discussing death and dying with patients is unsuitable due to the potential for causing stress and anxiety and negatively affecting patient morale [56]. This aspect is evident in studies conducted to assess death anxiety among Iranian cardiovascular patients as well [57][58][59].…”
Section: Key Findings Of the Studymentioning
confidence: 99%
“…In Iran, attention to end-of-life issues and problems can be enhanced through an approach called palliative care [ 10 ]. The study by Fereidouni et al in Iran indicated that in order to support patients, care providers and families of patients, the place where palliative care is provided for patients at the end-of-life should be compatible with their wishes and preferences [ 11 ]. Furthermore, elderly patients at the end-of-life should share their preferences with others around them, or choose a person as a proxy decision-maker [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In one study found that Muslim people put off uncomfortable conversations about care planning until they become ill or suddenly become unable to express their wishes [ 18 ]. Despite the interesting of Muslim community in learning and receiving the concept of ACP [ 19 ], ACP in Iran, does not exist in a coherent way, but researchers and clinician have separately and limitedly investigated the dimensions of it, including palliative care [ 10 , 20 ] and hospice care [ 15 , 21 ], preferred place of care and preferred place of death [ 11 ], have a kind of ADs as Vasiyyah [ 22 ], and do not resuscitation [ 23 ] in their practice and research [ 24 ].…”
Section: Introductionmentioning
confidence: 99%